Eksistensi Sentra Kerajinan Tembaga Desa Tumang: Strategi Bertahan dalam Dinamika Zaman - Ariq Dwi Yulian Nugroho; Atika Wijaya (Faculty of Social Science, Universitas Negeri Padang, 2025)
Copper and brass crafts in Tumang Village, Cepogo District, Boyolali Regency, remain the mainstay of the community's economy. Unlike many other traditional craft centers that have declined due to their inability to adapt, Tumang has continued to develop and become known as the largest metal craft center in Indonesia. This study explains the survival strategies of the copper and brass craft industry in Tumang Village. The main problems faced by craftsmen are global competition, limited workforce regeneration, and the need to adapt to developments in digital technology. This study was conducted in July–August 2025 using qualitative methods, namely a research approach that focuses on an in-depth understanding of social phenomena from the perspective of the research subjects. Research subjects included entrepreneurs, employee craftsmen, community leaders, and village government officials who have a direct relationship with the sustainability of the Tumang craft industry. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed descriptively qualitatively. The research findings indicate that survival strategies in Tumang include product design innovation, maintaining handmade quality, modernizing digital-based marketing systems, dividing roles between entrepreneurs and employees, integrating with the tourism sector, and regenerating the workforce through internships, educational collaborations, and extracurricular activities. These findings demonstrate that the survival of Tumang crafts relies not solely on past cultural heritage but also on the ability to adapt to social, economic, and technological changes. The implications of this research contribute to strengthening the literature on sustainability strategies for the traditional crafts industry in Indonesia while also offering practical perspectives for developing regional policies and empowering communities based on local wisdom.Keywords: Survival Strategy, Industrial Sustainability, Copper and Brass Crafts, Tumang Village, Creative Economy